Beginning ASP.NET 4.5 in C♯ and VB - Spaanjaars, Imar (Wrox beginning guides., 2013)
This book walks you through ASP.NET, Microsoft's technology for building dynamically generated web pages. This edition retains the highly accessible approach to building the Planet Wrox website example, an online community site featuring product reviews, picture sharing, and bonus content for registered users.